2015
DOI: 10.1007/s13277-015-3951-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-335 directly, while miR-34a indirectly modulate survivin expression and regulate growth, apoptosis, and invasion of gastric cancer cells

Abstract: miR-335 and miR-34a are two microRNAs (miRNAs) usually downregulated in gastric cancer (GC). But, their exact regulative roles were not fully elucidated. In this study, we studied the association between miR-335 and/or miR-34a expression and overall survival of GC patients and explored the regulative role of miR-335 and -34a over survivin expression and GC cell growth and invasion. Fifty patients with GC were regularly followed up from 2011 to 2015. miRNA microarray was used to examine the expression trend of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
2
34
1
Order By: Relevance
“…The low expression of tumor suppressors, miR‐1 and miR‐146a, was associated with vascular invasion, lymph node involvement, and distant metastasis, in addition to the poor prognosis of patients with GC. Downregulation of miR‐335 was determined to be appreciably associated with lymph node metastasis (LNM), invasion of lymphatic vessels, cell invasion, and metastasis via targeting of BCL‐w and SP1 . In addition, the tumor suppressors, miR‐125a and miR‐146a, are notably correlated with LNM, indicating that they should be prognostic elements of OS .…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers In Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…The low expression of tumor suppressors, miR‐1 and miR‐146a, was associated with vascular invasion, lymph node involvement, and distant metastasis, in addition to the poor prognosis of patients with GC. Downregulation of miR‐335 was determined to be appreciably associated with lymph node metastasis (LNM), invasion of lymphatic vessels, cell invasion, and metastasis via targeting of BCL‐w and SP1 . In addition, the tumor suppressors, miR‐125a and miR‐146a, are notably correlated with LNM, indicating that they should be prognostic elements of OS .…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers In Gcmentioning
confidence: 99%
“…Downregulation of miR-335 was determined to be appreciably associated with lymph node metastasis (LNM), invasion of lymphatic vessels, cell invasion, and metastasis via targeting of BCL-w and SP1. 88,89 In addition, the tumor suppressors, miR-125a and miR-146a, are notably correlated with LNM, indicating that they should be prognostic elements of OS. 90,91 Furthermore, the relative level of miR-146a expression was an independent predictive factor for OS.…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers In Gcmentioning
confidence: 99%
“…However, gene-specific approaches suggest that miRNA-335-5p is downregulated in GC and clinically associated with advanced TNM stage and worse prognosis [5,33]. Functional studies have shown that exogenous expression of miRNA-335-5p deregulated many biological cell processes such as cell cycle, proliferation, apoptosis, migration, invasion, and metastasis [5,25,33,34] (Figure 2). Figure…”
Section: Mirna-335-5p and Gastrointestinal Malignanciesmentioning
confidence: 99%
“…Cellular processes by which miRNA-335-5p contributes to their regulation though of different target genes in gastric cancer cell lines. miRNA-335-5p inhibits tumorigenicity, cell cycle, proliferation, apoptosis, migration, invasion, and metastasis [5,25,33,34]. Abbreviations: CRKL, V-crk avian sarcoma virus CT10 oncogene homolog-like; CDH11, cadherin 11; PLAUR, plasminogen activator urokinase receptor; SP1, specificity protein 1; BCL-w, BCL2-like 2 (taken from Sandoval-Bórquez et al [5] with permission).…”
mentioning
confidence: 99%
“…However, the pooled P values did not support these associations. The P values of the associations between the expression of mir-200c with lymph node metastasis and TNM stage (9, 10), mir-34a with lymph node metastasis (11,12), as well as mir-215 with tumor invasion depth (13,14) changed from less than 0.05 to more than 0.05 (Tab. 2).…”
Section: Ncrna and Clinical Pathological Features Of Gastric Cancermentioning
confidence: 99%